High hydrostatic pressure-induced inactivation of bacterial spores. (February 2015) - Sarker, Mahfuzur R.; Akhtar, Saeed; Torres, J. Antonio; Paredes-Sabja, Daniel
Abstract High hydrostatic pressure (HHP) is the most-widely adopted novel non-thermal technology for the commercial pasteurization of foods. However, HHP-induced inactivation of bacterial spores remains a challenge due to spore resistance to the treatment limits of currently available industrial HHP units (i.e. ∼650 MPa and 50 °C). Several reports have demonstrated that high pressure can modulate the germination machinery of bacterial spores, rendering them susceptible to subsequent inactivation treatments. Unfortunately, high pressure-induced germination is a unique phenomenon for spores of the genus Bacillus but not of Clostridium. Alternative strategies to inactivate bacterial spores at commercially available pressure and temperature levels include promoting the germination step by inclusion of known germinants into the food formulation to increase the lethality of HHP treatments on bacterial spores. The aim of this review is to provide an overview of the molecular basis involved in pressure-triggered germination of bacterial spores and of novel strategies to inactivate bacterial spores with HHP treatments.